2002
DOI: 10.2527/2002.80123x
|View full text |Cite
|
Sign up to set email alerts
|

Lactation curves of commercial ewes rearing lambs2

Abstract: Three-hour milk production measurements determined by machine milking at 3-d intervals throughout a 63-d lactation period were used to describe lactation curves for crossbred ewes lambing at 1 and 2 yr of age and rearing single and twin lambs. Age of ewe, type of rearing, and day of lactation affected (P < 0.05) milk production. Over the 63-d lactation, average daily milk production was 2.56 and 2.63 kg, respectively, for 1- and 2-yr-old ewes rearing single lambs and 2.73 and 3.47 kg, respectively, for 1- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
3
13
1
5
Order By: Relevance
“…Ewes nursing single lambs presented higher average daily milk production (P<0.05), contrarily to the findings of Snowder & Glimp (1991), Ramsey et al (1998) and Cardellino & Benson (2002), who observed higher productions for ewes nursing twins.…”
Section: Resultscontrasting
confidence: 39%
“…Ewes nursing single lambs presented higher average daily milk production (P<0.05), contrarily to the findings of Snowder & Glimp (1991), Ramsey et al (1998) and Cardellino & Benson (2002), who observed higher productions for ewes nursing twins.…”
Section: Resultscontrasting
confidence: 39%
“…Means within a column with different letters differ (P < 0.05). Cardellino and Benson (2002) who observed that TPY occur at the fifth week of lactation period for one-and two-year-old ewes rearing single and twin lambs. Gaddour et al (2007) mentioned that there are evident differences in the dairy ability of different racial groups subjected to the same environmental and feeding conditions.…”
Section: Tpy (D)mentioning
confidence: 99%
“…Bu işlemler saat 20.00 de tekrarlanmış ve akşam süt verimi tespit edilmiştir. Sabah ve akşam sağılan süt miktarları toplanarak koyunların günlük süt verimi bulunmuştur (7,8).…”
Section: Materyal Ve Metotunclassified
“…Elle sağım, makineli sağım, oksitosin enjeksiyonu + makineli sağım ve tart-emzir-tart bu yöntemler arasındadır (1,7,8,16,19). Türkiye' de koyunlarda süt verimi ile ilgili çalışmalarda genellikle elle sağım yöntemi kullanılmıştır.…”
Section: Introductionunclassified
See 1 more Smart Citation